GMAT Question of the Day - Daily to your Mailbox; hard ones only

 It is currently 22 Oct 2019, 06:54

### GMAT Club Daily Prep

#### Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

# If ak - b = c - dk, then k =

Author Message
TAGS:

### Hide Tags

Math Expert
Joined: 02 Sep 2009
Posts: 58429
If ak - b = c - dk, then k =  [#permalink]

### Show Tags

17 Oct 2018, 02:39
00:00

Difficulty:

15% (low)

Question Stats:

94% (00:42) correct 6% (00:29) wrong based on 42 sessions

### HideShow timer Statistics

If ak - b = c - dk, then k =

A. b + c - a - d

B. (b + c + d)/a

C. c/a + b/d

D. (b − c)/(a − d)

E. (b + c)/(a + d)

_________________
GMAT Club Legend
Joined: 12 Sep 2015
Posts: 4017
Re: If ak - b = c - dk, then k =  [#permalink]

### Show Tags

17 Oct 2018, 06:32
Top Contributor
Bunuel wrote:
If ak - b = c - dk, then k =

A. b + c - a - d

B. (b + c + d)/a

C. c/a + b/d

D. (b − c)/(a − d)

E. (b + c)/(a + d)

GIVEN: ak - b = c - dk
Add b to both sides: ak = c - dk + b
Add dk to both sides: ak + dk = c + b
Factor left side: k(a + d) = c + b
Divide both sides by (a+d) to get: k = (c + b)/(a + d)

Cheers,
Brent
_________________
Test confidently with gmatprepnow.com
VP
Joined: 31 Oct 2013
Posts: 1465
Concentration: Accounting, Finance
GPA: 3.68
WE: Analyst (Accounting)
Re: If ak - b = c - dk, then k =  [#permalink]

### Show Tags

17 Oct 2018, 13:38
Bunuel wrote:
If ak - b = c - dk, then k =

A. b + c - a - d

B. (b + c + d)/a

C. c/a + b/d

D. (b − c)/(a − d)

E. (b + c)/(a + d)

Given ,

ak -b = c - dk

ak + dk = c +b

k ( a + d) = b + c

$$k = \frac{b + c}{a + d}$$

Intern
Joined: 28 May 2018
Posts: 1
Re: If ak - b = c - dk, then k =  [#permalink]

### Show Tags

17 Oct 2018, 23:42
Hi, Bunuel How can the answer be A?
Math Expert
Joined: 02 Sep 2009
Posts: 58429
Re: If ak - b = c - dk, then k =  [#permalink]

### Show Tags

18 Oct 2018, 00:46
charlottezhang wrote:
Hi, Bunuel How can the answer be A?

_________________________
It's E. Edited. Thank you.
_________________
Target Test Prep Representative
Status: Founder & CEO
Affiliations: Target Test Prep
Joined: 14 Oct 2015
Posts: 8125
Location: United States (CA)
Re: If ak - b = c - dk, then k =  [#permalink]

### Show Tags

18 Oct 2018, 18:16
Bunuel wrote:
If ak - b = c - dk, then k =

A. b + c - a - d

B. (b + c + d)/a

C. c/a + b/d

D. (b − c)/(a − d)

E. (b + c)/(a + d)

Simplifying, we have:

ak - b = c - dk

dk + ak = c + b

k(d + a) = c + b

k = (c + b)/(d + a)

_________________

# Scott Woodbury-Stewart

Founder and CEO

Scott@TargetTestPrep.com
122 Reviews

5-star rated online GMAT quant
self study course

See why Target Test Prep is the top rated GMAT quant course on GMAT Club. Read Our Reviews

If you find one of my posts helpful, please take a moment to click on the "Kudos" button.

Re: If ak - b = c - dk, then k =   [#permalink] 18 Oct 2018, 18:16
Display posts from previous: Sort by